Klasifikasi Kompetensi Alumni Berdasarkan Masa Tunggu Alumni untuk Mendapatkan Pekerjaaan Menggunakan Metode Agoritma C4.5 - Rizqia Cahyaningtyas; Luqman Luqman; Yolana Inas H (KILAT, 2020)
Tracer Study is a search for information about alumni that aims to identify how much higher education graduates can move in the world of work according to the relevance of their education. In this study, tracer study data were obtained from a questionnaire distributed to alumni. The data consists of data from the last 5 years, namely 2015 to 2019, which is processed to find out how long the alumni have to wait for a job from the time of graduation based on competency. C4.5 algorithm is used to form a decision tree to see which competencies have the most influence on alumni in order to get a job in a short time. The results of the analysis carried out there are several competencies that most influence the waiting period of alumni to get a job, namely disciplinary education, time management, analytical skills and computer skills. The highest accuracy was found in 2016, which was 82.86%.